The Effect of Financial Risk Analysis on Sustainable Village Development in Jayapura Regency - Maylen K. P. Kambuaya; Pascalina V. S. Sesa; Alfius Warner Yores Marisan (Institut Bisnis dan Informatika Kesatuan, 2026)
This study examines the management of village funds as a strategic policy of the Indonesian government to accelerate rural development and improve community welfare following the enactment of Law Number 6 of 2014 concerning Villages. The increasing allocation of village funds has created challenges related to financial risk management, particularly the risk of fraud caused by weak internal controls, limited transparency, and low community participation. Therefore, this research aims to analyze the effect of financial risks, namely fraud and corruption risk, liquidity risk, compliance risk, and operational risk, on sustainable village development. The study employs a mixed quantitative and qualitative approach with an associative design to test causal relationships between variables. Data were collected through offline questionnaires distributed to village apparatus in Sentani District (Hinekombe), East Sentani District, West Sentani District, and Waibu District in Jayapura Regency. Data analysis was conducted using Partial Least Squares (PLS) with SmartPLS software and supported by textual analysis using Voyant Tools. The findings reveal that fraud and corruption risk negatively and significantly affect sustainable village development, while liquidity and compliance risks show no significant influence. Operational risk demonstrates a positive and significant effect. The study concludes that improving institutional capacity, transparency, and community participation is essential to support sustainable village development.